La ocupación de la Amazonía vista desde Venezuela - Trinca Fighera, Delfina (2006)
The occupation of Amazonia has formed part of the different modernities through which human history has evolved. The valorization it experiences, above all, from the last decades of the last century is related to the modernity that defines our contemporary world. The integration processes that Brazil and Venezuela are implementing in their common border are a manifest proof that both governments are aware of the interest that Amazonia arouses in our present world. This work is intended to demonstrate the existing relationships between the processes of the occupation of Amazonia and the different modernities, with the purpose of detecting the new forms of land use and how they relate to the elements that define the present history. All of this is viewed from a Venezuelan perspective.